Electronic Olfactory Sensor Based on A. mellifera Odorant‐Binding Protein 14 on a Reduced Graphene Oxide Field‐Effect Transistor - Larisika, Melanie (Angew Chem Int Ed Engl, 2015)
An olfactory biosensor based on a reduced graphene oxide (rGO) field‐effect transistor (FET), functionalized by the odorant‐binding protein 14 (OBP14) from the honey bee (Apis mellifera) has been designed for the in situ and real‐time monitoring of a broad spectrum of odorants in aqueous solutions known to be attractants for bees. The electrical measurements of the binding of all tested odorants are shown to follow the Langmuir model for ligand–receptor interactions. The results demonstrate that OBP14 is able to bind odorants even after immobilization on rGO and can discriminate between ligands binding within a range of dissociation constants from K (d)=4 μm to K (d)=3.3 mm. The strongest ligands, such as homovanillic acid, eugenol, and methyl vanillate all contain a hydroxy group which is apparently important for the strong interaction with the protein.